2010
DOI: 10.1185/03007995.2010.518135
|View full text |Cite
|
Sign up to set email alerts
|

Burden on UK secondary care of rotavirus disease and seasonal infections in children

Abstract: Rotavirus contributes to the significant burden that seasonal infections place on inpatient paediatric resources during the winter and spring months. This study may be limited by issues of clinical coding and the infrequency of confirmatory microbiological testing in real-world practice. Vaccination might be considered as a means of reducing this clinical and economic burden particularly where long-term effectiveness and ease of administration are proven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…for rotavirus, gonorrhoea, or varicella [32][33][34]. In Germany, ICD-10 codes have previously been used to assess the herpes zoster disease burden also in the outpatient sector [35], and to assess reporting completeness of notifiable disease surveillance systems [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…for rotavirus, gonorrhoea, or varicella [32][33][34]. In Germany, ICD-10 codes have previously been used to assess the herpes zoster disease burden also in the outpatient sector [35], and to assess reporting completeness of notifiable disease surveillance systems [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, Health Resource Group data are increasingly considered appropriate for use in health-care research. 15,16 Although it was not possible for the authors to validate all the data, the authors are directly involved in services in four major centres and found that the figures for their own centres generated by CHKS Ltd appeared to be appropriate. The use of routinely collected statistics has the weakness that the data are less detailed (eg, lack of information on indications for orbital decompression), but an important advantage is that it is comprehensive.…”
Section: Discussionmentioning
confidence: 99%
“…This trend results from seasonality of many common childhood infections that represent >40% of infant hospitalizations, creating a high seasonal pressure on pediatric resources. [1][2][3] Rotavirus (RV) is the most frequent cause of hospitalization due to viral gastroenteritis in young children; RV epidemics peak in winter and early spring overlapping with those of other seasonal infections. Acute gastroenteritis (AGE)-related hospitalizations during winter seasons are almost completely attributed to RV.…”
mentioning
confidence: 99%